2011
DOI: 10.1038/hdy.2011.103
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental genetic or phenotypic divergence and progeny variation in the maize nested association mapping population

Abstract: Appropriate selection of parents for the development of mapping populations is pivotal to maximizing the power of quantitative trait loci detection. Trait genotypic variation within a family is indicative of the family's informativeness for genetic studies. Accurate prediction of the most useful parental combinations within a species would help guide quantitative genetics studies. We tested the reliability of genotypic and phenotypic distance estimators between pairs of maize inbred lines to predict genotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
178
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(186 citation statements)
references
References 48 publications
5
178
2
1
Order By: Relevance
“…Wegary et al (2013) also reported that morphological distances were less important than molecular marker-based genetic distances for predicting the F 1 performance of heterosis and SCA effects for grain traits. Nevertheless, PD was a better predictor of gene variance than GD across a 26 maize bi-parent group for 19 traits (Hung et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Wegary et al (2013) also reported that morphological distances were less important than molecular marker-based genetic distances for predicting the F 1 performance of heterosis and SCA effects for grain traits. Nevertheless, PD was a better predictor of gene variance than GD across a 26 maize bi-parent group for 19 traits (Hung et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Among the sample of families from across 10 generations, averaged across nine environments, the timing from planting to silking and anthesis spanned 37 and 27 days, respectively; PLHs ranged from 162 to 267 cm, and ERHs ranged from 73 to 182 cm. The range and magnitude of genotypic variation found here in Hallauer's Tusón exceeded or was comparable to that of the diverse multi-parent NAM population (Buckler et al, 2009;Hung et al, 2012a). The NAM population was designed to maximize the sampling of molecular diversity and has been used to identify numerous loci associated with variation in the aforementioned traits.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of inbred lines evaluated in field experiments was 5,481. Details of experimental design and phenotype data analysis are provided in the work of Hung et al (38) and in SI Appendix, SI Materials and Methods. Each NAM and IBM line was genotyped with a common set of 1,106 SNP markers chosen to have high informativeness in these crosses (14).…”
Section: Methodsmentioning
confidence: 99%
“…The maize NAM population was created by crossing 25 diverse inbred lines to the common reference parent B73 and deriving 200 RILs from each cross to form 5,000 mapping lines (14). The NAM population was evaluated in 11 environments, including eight environments with mean day lengths greater than 13 h during the growing season (long-day length environments) and three environments with mean day lengths less than 13 h (short-day length environments) (38). A sample of 200 intermated B73 × Mo17 (IBM) RILs (39) and a panel of 281 lines encompassing much of the global diversity of public maize inbreds ("maize association panel") (32) were also included alongside the NAM lines in field evaluations.…”
Section: Methodsmentioning
confidence: 99%